An innovative variable target time method for probabilistic-based seismic performance assessment of multi-storey buildings. (15th July 2022) - Mohsenian, Vahid; Gharaei-Moghaddam, Nima; Hajirasouliha, Iman
Abstract: Incremental dynamic analysis is one of the most widely used methods to develop fragility curves due to its ability to deal with various inherent uncertainties in the prediction of earthquake recurrence and characteristics. The dependence of the results to the selected ground motion records, uncertainties associated with the selection of appropriate earthquake input records and high computational costs are among the challenges limit the practical applications of this method. In this study, an innovative variable target time (VTT) method is developed based on the concept of endurance time (ET) analysis for structural reliability assessment of 3D multi-storey structures. A novel low-computational cost process is proposed to develop the database of desired statistical population and estimate the probabilities for constant hazard levels (EDP-based method) by taking into account the uncertainties in the frequency content of the input earthquakes. To verify the accuracy of the outcomes, the results are compared with the fragility curves derived based on different damage levels (IM-based method) and Incremental Dynamic Analysis (IDA) for moment-resisting steel and tunnel-from concrete 3D structures with 5- and 10-storeys. The results indicate that the proposed method is capable of providing highly accurate probabilistic models for structural performance under different levels of earthquake intensity. For the selected steel moment-resisting structures, the maximum difference in the reliability results obtained by the two methods of analysis for the Immediate Occupancy (IO), Life Safety (LS), and Collapse Prevention (CP) performance levels under the Design Basis Earthquake (DBE) and the Maximum Considered Earthquake (MCE) are around 2, 7 and 5%, respectively. Similarly, the reliability results for the 3D tunnel-from concrete structures show around 6, 7, and 6% errors between the two analysis methods for the IO, LS and CP performance levels, respectively. The proposed method reduces the computational costs of the IDA-based methods by 80%, and hence, can be considered as a suitable alternative for the conventional methods to develop fragility curves of 3D structures. Highlights: A variable target time method is proposed for seismic performance assessment of 3D buildings based on ET Method The efficacy of the method is demonstrated for 5 and 10-storey moment-resisting steel and tunnel-from concrete structures For different performance levels, fragility curves obtained by conventional and proposed methods are less than 7% different Compared to conventional IDA-based methods, the proposed method reduces the computational costs by 80% The proposed method can be efficiently used for fragility analyses regardless of the adopted lateral load resisting system